Sozialpolitik im EU-Mehrebenensystem Europäisierung einer nationalen Domäne? - Windwehr, Jana (Verlag Barbara Budrich, 2022)
The EU's multi-level system continuously renegotiates the influence of the European institutions on national sovereignty. Social policy has traditionally been the domain of the member states. But is it still possible to speak of the political autonomy of the nation-states, or is the European level gaining in importance through social and budgetary policy measures, some of which are restrictive? Jana Windwehr vividly analyzes Europeanization processes within social policy in the context of the euro crisis, using five member states as examples. This makes the book an indispensable contribution to the discussion on national social policy autonomy in the EU multi-level system.